2020
DOI: 10.1002/eco.2251
|View full text |Cite
|
Sign up to set email alerts
|

Detection and attribution of lake water loss in the semi‐arid Mongolian Plateau—A case study in the Lake Dalinor

Abstract: Extensive lake shrinkages have been observed in the semi‐arid Mongolian Plateau over the past several decades, causing a great challenge to the local socio‐economic sustainability and ecological security. However, issue on the dominant drivers of this water loss has not been well addressed. In this work, variations in water area and water level of the Lake Dalinor during the period 1984–2018 were tracked using the satellite altimetry and Landsat images. Dominant drivers for the derived variations were then inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…On the contrary, Li et al (2017) found that decreasing precipitation drove the reduction of the Dalinor Lake basin, while rising temperature and vegetation greenness accelerated this trend. Bai et al (2021) concluded that climate change and anthropogenic impacts contributed 76.5 and 23.5% of the observed lake area declining trend according to the model‐based attribution analysis. Wei (2019) also found that the water surface of the Dalinor Lake was significantly correlated with the annual precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Li et al (2017) found that decreasing precipitation drove the reduction of the Dalinor Lake basin, while rising temperature and vegetation greenness accelerated this trend. Bai et al (2021) concluded that climate change and anthropogenic impacts contributed 76.5 and 23.5% of the observed lake area declining trend according to the model‐based attribution analysis. Wei (2019) also found that the water surface of the Dalinor Lake was significantly correlated with the annual precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Soil water movement is described using the layered water balance equation derived from the discretized Richards equation. The VIP model has been successfully applied to ecohydrological studies in North China Plain (Hu et al, 2014; Mo, Liu, Lin, & Guo, 2009; Mo et al, 2017), North‐eastern China (Mo et al, 2014) and the Loess Plateau (Bai et al, 2019; Liu et al, 2009; Mo, Liu, Chen, et al, 2009), as well as the endorheic Mongolian Plateau (Bai et al, 2020). Details of the VIP model can be seen in Mo, Beven, et al (2004) and Mo, Liu, et al (2004).…”
Section: Materials and Methodologymentioning
confidence: 99%
“…The Hulunbuir forest-steppe ecotone is a channel for water resources exchange between two important ecological function areas and an important ecological barrier area in the north of China, which is of strategic importance for maintaining sustainable development and water resources management planning in northeast and even north China. However, the water conservation of the Hulunbuir foreststeppe ecotone has decreased in the past 20 years, which indicated the deterioration of the ecological environment in this area [10][11][12][13]. Therefore, it is necessary to strengthen the awareness of the ecological environment and water resources protection and take effective measures in time.…”
Section: Significance and Limitations Of This Studymentioning
confidence: 99%
“…In recent years, data from several studies suggested that the forest-steppe ecotone was disturbed by global climate change and human activities resulting in significant variations in landscape patterns, severe aridity of habitats, drying of lakes, shrinking wetlands, and decreasing water yield [10][11][12][13][14][15]. These phenomena have become significant ecological problems restricting the sustainable development of regional resources, environment, and social economy.…”
Section: Introductionmentioning
confidence: 99%